A Mathematical Model for Temperature Induced Loosening due to Radial Expansion of Rectangle Thread Bolted Joints. (January 2015) - Hou, Shiyuan; Liao, Ridong; Li, Jishan
This paper proposed a mathematical model to investigate the radial expansion induced loosening of rectangle thread bolted joints that were subjected to cyclic temperature variation, which could cause slippage between contact pairs of engaged threads and bolt bearing. Firstly, integral equations were derived for the shear stress components caused by expansion difference, as well as the bearing and thread friction torque components, which depended on the temperature variation. Secondly, the relationship of displacement components was developed based on quasi-static hypotheses. Then, treating the rotation of bolt as plastic elongation, the bolt tension's evolution was obtained by using a one-dimensional bolted joint model. Numerical results showed that the temperature variation decreased the bearing and thread friction torque components, which could lead bolted joint to loosen. Finally, the effects of some associated factors on the progress were discussed.